Importance of digital educational resources for university training in management: A review of the literatura - Mejia Uquiche, Yasser David (2025)
The business world is constantly evolving, and future management professionals who possess digital skills and a command of technological resources will be afforded greater opportunities for academic and professional growth. This research aims to highlight the importance of digital educational resources in the teaching and learning process for the Bachelor’s degree student in Management. The methodology used was a literature review of 25 highly relevant scientific articles in the Latin American context according to the proposed topic. The time period covers the last five years, from 2021 to 2025. The analysis of these elements made it possible to present the results divided into three sections, the first: digital platforms, the second: business simulators, and the third: Artificial Intelligence (AI) and subsequently the development of the discussion. It was concluded that knowing how to use digital resources allows students to develop management skills and gain a competitive advantage in their future careers. This manuscript is derived from the research of the master’s thesis, Digital Educational Resources and English Language Learning at the Faculty of Administrative Sciences UNMSM 2024-I.